ECONOMIC ACTIVITIES IN A MATRILINEAL CULTURE: A CASE STUDY OF THE TRAVELING MARCHANT IN MINANGKABAU VILLAGES IN INDONESIA - Silfia Hanani; Delvi Wahyuni (Marwah: Jurnal Perempuan, Agama dan Jender, 2013)
This paper seek to highlight economic activities in a matrilineal culture. Matrilineal cultural system has given enormous privileges forMinangkabau women. They have the right to manage the communal property. As the result, the practice of this culture promotes economic independence amongs Minangkabau people. There are three typical characteristics enclosed to this ethnic. First, Minangkabau people are keen practitioners of merantau (going overseas/leaving native places) tradition. Second, Islam is this ethnic official religion and the third, this ethnic practices matrilineal cultural system. This paper observes the activities ofMinangkabau women who travel from one to other traditional markets as merchants which begins to gain popularity as a profession for Minangkabau women in the outset of Asian 1997 monetary crisis. Sikaladi was chosen as the research location of this study. Sikaladi is a jorong (a sub village) within the nagari of Pariangan The result show that, traveling as merchants can be promulgate as a semi-merantau activity. Those women leave their village on the basis and return in the same day. Currently, it has been noted that there are 69 woman traveling merchants in this jorong which means 40%of the overall women population of the jorong are traveling merchants. This situation suggests that these women involvement in economic activities has saved the course of their family from the disastrous storm of the 1997 monetary crisis. Further, it reduces the degree of poverty in this region. Most importantly, it also reduces the number of unemployment among women of productive age in Sikaladi.